Establishment of Immortalized Human Hepatocytes by Introduction of HPV16 E6/E7 and hTERT as Cell Sources for Liver Cell-Based Therapy - Tsuruga, Yosuke; Kiyono, Tohru; Matsushita, Michiaki; Takahashi, Tohru; Kasai, Hironori; Todo, Satoru (Cell transplantation, 2008)
For future cell-based therapies for liver diseases, the shortage of cell sources must be resolved. Immortalized human hepatocytes are expected to be among the new sources. In addition to telomerase activation by the introduction of human telomerase reverse transcriptase (hTERT), inactivation of the p16/RB pathway and/or p53 by E6/E7 of human papillomavirus type 16 (HPV16) has been shown to be useful for efficient immortalization of several human cell types. Here we report the immortalization of human hepatocytes by the introduction of HPV16 E6/E7 and hTERT. Human adult hepatocytes were lentivirally transduced with HPV16 E6/E7 and hTERT. Two human immortalized hepatocyte cell lines were established and were named HHE6E7T-1 and HHE6E7T-2. Those cells proliferated in culture beyond 200 population doublings (PDs). Albumin synthesis and expression of liver-enriched genes were confirmed, but gradually decreased as passages progressed. Karyotype analysis showed that HHE6E7T-1 cells remained near diploid but that HHE6E7T-2 cells showed severe aneuploidy at 150 PDs. Subcutaneous injection of these cells into severe combined immunodeficiency (SCID) mice did not induce tumor development. Intrasplenic transplantation of dedifferentiated HHE6E7T-1 cells over 200 PDs significantly improved the survival of acetaminophen-induced acute liver failure SCID mice. In conclusion, we successfully established immortalized human hepatocytes that retain the characteristics of differentiated hepatocytes. We also showed the reduction of hepatocyte-specific functions in long-term culture. However, the results of intrasplenic transplantation to SCID mice with acetaminophen-induced acute liver failure showed the possibility of HHE6E7T-1 serving as a cell source for hepatocyte transplantation.